Rumble in the jungle - STILTON, GERONIMO (New York Scholastic, 2011)
The "Rumble in the Jungle" was a historic heavyweight boxing match on October 30, 1974, in Kinshasa, Zaire, where underdog Muhammad Ali knocked out the undefeated champion George Foreman in the eighth round.
English